2014
DOI: 10.1038/cgt.2013.79
|View full text |Cite
|
Sign up to set email alerts
|

Combination of adenoviruses expressing melanoma differentiation-associated gene-7 and chemotherapeutic agents produces enhanced cytotoxicity on esophageal carcinoma

Abstract: We examined the combinatory antitumor effects of adenoviruses expressing human mda-7/IL-24 gene (Ad-mda-7) and chemotherapeutic agents on nine kinds of human esophageal carcinoma cells. All the carcinoma cells expressed the melanoma differentiation-associated gene-7/interleukin-24 (MDA-7/IL-24) receptor complexes, IL-20R2 and either IL-20R1 or IL-22R1, and were susceptible to Ad-mda-7, whereas fibroblasts were positive only for IL-20R2 gene and resistant to Ad-mda-7-mediated cytotoxicity. Sensitivity of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Delivery of therapeutic viral vectors into the target organ and tumor is required for the treatment of lung cancer or esophageal cancer [ 41 43 ]. One of the drawbacks of this approach is the lack of means to effectively deliver the therapeutic virus to target different kinds of cells that reside within an intricate lung and esophageal structure.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of therapeutic viral vectors into the target organ and tumor is required for the treatment of lung cancer or esophageal cancer [ 41 43 ]. One of the drawbacks of this approach is the lack of means to effectively deliver the therapeutic virus to target different kinds of cells that reside within an intricate lung and esophageal structure.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted rhIL-24 by normal cells inhibits invasion and sensitizes specific cancer cells containing functional IL-20R to radiation (19). With regard to ESCC, Ma et al (20) reported that Ad-IL-24 enhanced agent-mediated cytotoxicity in certain cell lines (TE-1, TE-2, TE-10, TE-11, YES-2, YES-4, YES-5, YES-6 and T.Tn cells), and the combination with 5-fluorouracil, cisplatin, mitomycin and etoposide produced greater antitumor effects than monotherapy. Our previous study showed that the human IL-24 peptide created by computer-guided design contributed to suppression of proliferation in ESCC Eca-109 cells (21).…”
Section: Secreted Recombinant Human Il-24 Protein Inhibits the Prolifmentioning
confidence: 99%
“…Although IL20RB was initially found to be involved in many nonmalignant diseases, such as psoriasis [ 16 ], rheumatoid arthritis [ 17 ], vitiligo [ 18 ], ulcerative colitis [ 19 ], glaucoma [ 20 ], asthma [ 21 ], endometriosis [ 22 ], and chronic rhinosinusitis [ 23 ] as well as infectious diseases [ 24 ], novel discoveries indicate IL20RB could also play an important role in malignant diseases. Recently, increasing evidence supports IL20RB also plays a vital role in human cancers such as colorectal adenocarcinoma [ 25 ], breast cancer [ 26 ], and esophageal carcinoma [ 27 ], while its role in ccRCC still remains unclear.…”
Section: Introductionmentioning
confidence: 99%